Capacity planning problem in advanced manufacturing systems - Cilacı, Ayşe (My University, 1999)
The objective of this thesis is to study capacity planning problem in a randomly driven advanced manufacturing system. The thesis is focused on capacity planning methodology and features of advanced manufacturing systems to be considered during planning process. Among the various planning techniques and tools, simulation modeling and experimenting is found and applied as the most appropriate one. The model approach and the experiments used have been found as a useful guide in capacity planning in advanced manufacturing systems design.

Bu tezin hedefi, stoğa üretim yapan ileri imalat sistemlerinde kapasite planlama problemini incelemektir. Tezde, planlama sürecinde göz önünde bulundurulması gereken kapasite planlama teknikleri ve ileri imalat sistemlerinin özellikleri üzerinde yoğunlaşılmıştır. Tezde kullanılan simulasyon modelleme yaklaşımı ve deneysel tasarımları, ileri imalat sistemlerinde kapasite planlama sürecinde yol gösterici olacaktır.
Keywords: FABRİKA MÜHENDİSLİĞİ